Contextual Approach Animated Video in Science Material for Grade Fourth Elementary School Students - Ni Putu Ari Mardanti; Ida Bagus Gede Surya Abadi (Indonesian Journal Of Educational Research and Review, 2021)
Lack of learning support materials and the need for media development to assist teachers in explaining learning materials. Learning is only based on the theme book. Therefore, it is necessary to develop animated videos with a contextual approach to the content of science material. This study aims to develop an animated video learning media with a contextual approach to the content of science material. This type of research is the development of the ADDIE model development research model. Data collection methods used are questionnaires or questionnaires, interview methods, and document recording methods. Data analysis techniques used are qualitative analysis techniques and quantitative analysis techniques. The subject of this research is the development of animated video media. The results of this study are a description of the design and development of animated video media with a contextual approach in the form of product development documentation and validation according to subject content experts' reviews which obtained a score of 100% very good qualification, a review of learning design experts obtained a score of 97% with very good qualifications. Learning media expert reviews obtained a score of 97% with very good qualifications, and media expert reviews were obtained by 97.3% with very good qualifications and group expert reviews with 98.67% gains with very good qualifications. So it can be said as the development of animated video media with a contextual approach is very well used in fourth-grade science material in elementary schools. The research implication is that contextual approach animation video media can help students in learning.